Modern Irish drama : W.B. Yeats to Marina Carr - Sternlicht, Sanford, 1931- (Irish studies (Syracuse, N.Y.), 2010)
"Achieves what heretofore seemed unachievable, making sense for the non-Irish reader of the convolutions and contradictions of Irish drama that mirror the history and life of the country."ùChristopher Fitz-Simon, author of The Irish Theatre